Evaluation of Captive Bolt for Emergency Field Euthanasia in Canada Geese. (21st December 2021) - Shearer, Karen E.; Brook, Rodney W.; Sharp, Christopher M.
ABSTRACT: In rare circumstances during research or monitoring operations for wild birds, emergency euthanasia is required. However, standard methods of euthanasia may not be humane for large birds. We evaluated the use of a Dick KTBG® spring‐powered, penetrating captive bolt for the euthanasia of Canada geese ( Branta canadensis ). We conducted trials on hunter‐harvested geese to determine anatomical placement of the device and to assess skull and brain penetration effectiveness. We then assessed the device for euthanasia on anesthetized geese. Although results using dead geese suggested the device may be effective (i.e., consistent skull penetration, and trajectory depth into relevant brain structures), we found the device did not produce consistent, humane euthanasia for anesthetized geese and was not suitable for emergency field euthanasia for Canada geese. We encourage further evaluations of emergency euthanasia methods using a 2‐step process of determining placement and efficacy on dead birds and then testing on live anesthetized individuals. © 2021 The Wildlife Society. Abstract : Wildlife researchers must prepare for rare circumstances when emergency field euthanasia may be necessary. Minimal data is available for emergency euthanasia of wildlife. We used a 2‐step process to evaluate a spring‐powered captive bolt for emergency field euthanasia of Canada goose ( Branta canadensis ).